Application of Problem Based Learning (ABP) by John Barell in literal understanding - Hurtado Serna, Mirian (2020)
The study for consideration shows the importance of problem-based learning that was developed under the quantitative approach, of quasi-experimental design, the objective was to verify the effects of the application of literal problem-based learning (ABP) in schoolchildren of the level Primary of the 4th grade of the Educational Institution of Peru. In order to know the effects of the ABP, the students of the experimental group were asked: challenges, curiosities, uncertainty about the phenomena or problems of daily life through the three units of the ABP, following the ten steps John Barell sequentially with the In order to motivate students to become involved in reading by looking for information that allows them to solve the challenges posed, while the control group developed their classes on a regular basis. The results obtained show that 74,07% of the students in the experimental group are at the outstanding achievement level, and 25,93% in the expected achievement compared to 14,81% of the control group who are at the expected achievement level and 85,2% in the two lower levels (process and onset), this comparison was evidenced by the Mann-Whitneya U test whose contrast results were p <0.05. Who allowed to affirm that the problem-based learning of John Barrel has a significant effect on literal understanding.